SATISFACTION ON DELIVERY CARE SERVICES AMONG RURAL WOMEN IN SARAWAK, MALAYSIA: A CROSS-SECTIONAL COMMUNITY-BASED STUDY - Md Mizanur Rahman; Deburra Peak Ngadan; Mohd Taha Arif (Universitas Airlangga, 2020)
The improvement of quality in maternity care services is an effective strategy to reduce maternal mortality. The utilisation of the maternity services and its satisfaction indirectly measure the quality of services. This study aimed to assess the level of satisfaction with delivery care and also to identify the factors influencing the satisfaction among women on the quality of delivery care services in Sarawak. A cross-sectional study was conducted in the three main zones of Sarawak, Malaysia. A total of 1236 completed data were analysed. Data was collected using the validated Patient Satisfaction Questionnaire (PSQ-18, Short Form) by face to face interview. Data entry and analysis was done by SPSS version 22.0 software. A p-value of less than 0.05 was considered statistically significant. A multinomial logistic regression analysis revealed that Bidayuh ethnics were 28.6% less likely to have good satisfaction with delivery care than the other ethnic groups. The respondents were 1.806 times more likely to have the average satisfaction and 1.972 times more likely to have good satisfaction on delivery care if a doctor attended the latter. Similarly, the respondents were 2.29 times highly satisfied if the out of pocket expenses were less than MYR 91.50 (US 21.73) compared to 2.10 times in average satisfaction. Overall, the women were satisfied with the delivery care services. However, assessment of satisfaction with the services provided from the different level of health care professionals needs to be explored to gain a deeper understanding of maternal care.Keywords: Delivery Care, Level of satisfaction, Maternal Health Services, Sarawak.